A Review on Single Phase AC System of Railway Electrification - Sah, Rupesh Kumar; Gautam, Basanta Kumar (International Journal on Engineering Technology, 2024)
The widespread adoption of 25 kV, 50 Hz single-phase AC supply in long-distance electrified railway systems poses significant challenges to power quality in transmission networks. This paper presents an in-depth investigation into the influence of electric railway systems on a 110 kV transmission system, with a specific focus on locomotives equipped with diode rectifiers. Harmonic currents generated by these locomotives and unbalanced voltages introduced by single-phase traction loads are known to adversely affect power system components, leading to issues such as overheating, additional losses, and interference with communication systems. The focus of this paper is not only to understand the fundamental principles but to conduct a deep exploration of the functioning of various components such as locomotives, contact lines, and substations. High voltage This voltage is supplied from the substation or directly from the generating station. This high AC voltage (25KV) is first transformed into low AC voltage (415V). Three-phase induction motors are used because they provide high torque, are reliable, and are more efficient. The AC voltage in the second phase is rectified to DC and then converted into a phase AC using VFD. The VFD provides variable frequency and voltage to run the induction motor at different speeds.